The Effects of nurse-managed ambulatory care (NMAC) on satisfaction of care among patients with rheumatic heart disease (RHD) at the Philippine Heart Center - Aldea, Maria Romina G.
This study mainly examined the effects of nurse-managed ambulatory care (NMAC) on satisfcation of care among RHD patients, who come for their follow-up care at the Outpatient Department (OPD) of Philippine Heart Center. This study was conducted: (1) to determine if NMAC improved activities of daily living, perception of care and physiologic variables among RHD patients; (2) to determine if sociodemographic data, namely, age, sex, education and support system were significantly related to activities of daily living, perception of care and physiologic variables; and (3) to determine the responses of RHD patients to NMAC. The post-test only control group design was utilized. A total of sixty-five (65) patients participated in the study through simple random sampling. Of these, thirty-two (32) patients belonged to the control group and thirty-three (33) patients belonged to the intervention group. The intervention involved direct nursing care consisting of physical assessment, patient education, nurse-patient interaction, and indirect nursing care which included coordination and referral.
Four types of patient visit to the OPD ocurred during the two-week period of the study. This consisted of consultation, follow-up, active treatment and referral. The following were the findings of the study. Forty-five (69.23%0 of the subjects were female and 20 (30.77%) were male, with a mean age of 30.26 years. Majority (n=44,67.69%) reached 6 to 10 years of education, with a mean of 9.214 yers. For the support system, greater number of patients (n=35, 53.85%) opted to approach their parents when not feeling well and most RHD patients had good and better support scores (mean=19.382). The findings of the study showed evidence that NMAC improved the perception of care among RHD patients (p=0.00006). Difference in the means of perception scores between the two groups was highly significant on nurse-patient interaction, followed by coordination of care, patient education and clinical skill of the nurse. There is evidence to support the benefits of the direct and indirect care activities performed by the nurse. The study group showed better results on their perception of care than the control group. However, the nurse's intervention yielded no improvement on physiologic variables (p>0.05) and on activities of dily living performance after one week (p=0.45).
Age of patients was negatively correlated with their vardiac rate (r= -0.248, p=0.046). Patients who performed their ADL independently after one week had significantly higher support scores (p=0.04). However, sex and years of education were not related to any of the indicators in satisfaction of care. Satisfaction of care as perceived by the patients in the study group can be attributed to the prompt attention and intensive one-on-one nurse-patient interaction. The nurse spent time (mean=19.12 minutes) for direct and indirect nursing care per patients' visit. This intervention helped the patients express their feelings about their illness and the impact it has on their adjustments in daily living. The provision of health education made them aware about the process of their illness and the preventive and restorative aspects of care. Referral of patients to the Emergency Room was reduced by providing treatments that could be administered in the OPD. Cost estimation in the OPD showed a reduction by 50% as compared to patients admitted to E.R.. Access to the telephone for inquiries directed to the nurse about their health care plan were cost-effective measures that reduced the use of E.R. facilities and assured continuity of care. There was no significant improvement on the satisfaction of care scores. The use of NMAC showed improvement in the perception of care among RHD patients. No improvement was seen on performance ADL and physiologic variables. Descriptive responses of patients indicate that the presence of the nurse in the OPD is highly needed to meet their health care needs.
Thesis (Master of Arts in Nursing) -- University of the Philippines Manila
Keywords: Ambulatory care; Patient satisfaction; Ambulatory care nursing; Rheumatic heart disease